Octogenarian Motor Vehicle Collisions: Injury Patterns Matter - Lemon, Michael; Helmer, Stephen; Soba, Kathryn; Ward, Jeanette; Haan, James M (Kansas Journal of Medicine, 2022)
Introduction. Motor vehicle collision (MVC) is the second most common mechanism of injury among octogenarians and is on the rise. These “oldest old” trauma patients have much higher mortality rates than expected. This study examined potential factors influencing this increased mortality including comorbidities, medications, injury patterns, and hospital interventions. Methods. A 10-year retrospective review was conducted of patients aged 80 and over who were injured in a MVC. Data collected included patient demographics, comorbidities, medication use prior to injury, collision details, injury severity and patterns, hospitalization details, outcomes, and discharge disposition. Results. We identified 239 octogenarian patients involved in a MVC. Overall mortality was 18.8%. We recognized an increased mortality for specific injury patterns, patients injured in a rural setting, and those who were transfused, intubated, or admitted to the ICU. We found no correlation between mortality and medications or comorbidities. Conclusions. The high mortality rate for octogenarian patients involved in a MVC is related to injury severity, type of injury, and in-hospital complications, and not due to comorbidities and prior medications.